Reduced Performance Due to Adenoviral Gizzard Erosion in 16-Day-Old Commercial Broiler Chickens in Iran, Confirmed Experimentally - Mirzazadeh, Amin; Grafl, Beatrice; Abbasnia, Mohammad; Emadi-Jamali, Sobhan; Abdi-Hachesoo, Bahman; Schachner, Anna; Hess, Michael (Frontiers in Veterinary Science, 2021)
Adenoviral gizzard erosion (AGE) in broilers is an emerging infectious disease with negative impact on flock productivity. Despite of known primary etiological role of fowl adenovirus serotype 1 (FAdV-1) in AGE, there are a limited number of field reports worldwide possibly, because the disease is less noticeable and clinically difficult to assess. The present study documents an outbreak of AGE in 16-day-old broiler chickens on a farm in the north of Iran and the reproduction of the disease in an experimental setting. In the field, a sudden onset of mortality was noticed in affected broilers resulting in 6% total mortality and decreased weight gain leading to approximately one-week delay to reach the target slaughter weight. Necropsy findings in dead broilers revealed black colored content in crop, proventriculus and gizzard together with severe gizzard erosions characterized by multiple black-brown areas of variable size in the koilin layer and mucosal inflammation. Microscopic examination revealed necrotizing ventriculitis marked with severe dissociation of koilin layer and degeneration of glandular epithelium with infiltration of mononuclear inflammatory cells. FAdV-1 was isolated from affected gizzards. Phylogenetic analysis of the hexon loop-1 (L1) sequence of the isolated virus showed 100% identity with pathogenic FAdV-1 strains previously reported from broiler chickens with AGE. Subsequently, an in vivo study infecting day-old commercial layer chickens with the field isolate demonstrated characteristic lesions and histopathological changes of AGE together with decreased weight gain in the infected birds. For the first time, the progress of a natural outbreak of AGE in Iran is described and experimental reproduction of the disease is demonstrated. The findings highlight the economic impact of the disease for regional poultry production due to mortality and impaired weight gain of the affected broilers.